Testing for boosting at the Paralympic games: policies, results and future directions - Blauwet, C. A.; Benjamin-Laing, H.; Stomphorst, J.; Van de Vliet, P.; Pit-Grosheide, P.; Willick, S. E. (British Journal of Sports Medicine, 2013)
Background `Boosting` is defined as the intentional induction of autonomic dysreflexia (AD) by athletes with a spinal cord injury (SCI) at or above the level of T6 for the purpose of improving sports performance. Boosting has been shown to confer up to a 9.7% improvement in race time. Additionally, to compete in a hazardous dysreflexic state, whether intentional or unintentional, would present an extreme health risk to the athlete. For these reasons, the International Paralympic Committee strictly bans the practice of boosting, and has developed a protocol to test for its presence.